1997
DOI: 10.1152/ajpregu.1997.273.1.r205
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain characteristics of muscle sympathetic nerve activity in heart failure and healthy humans

Abstract: The purpose of this study was to characterize oscillations in muscle sympathetic nerve activity (MSNA) in the frequency domain in healthy subjects and patients with congestive heart failure (CHF) and to relate these to blood pressure (BP), heart rate (HR), and breathing frequency. MSNA burst frequency was significantly greater in CHF [52 +/- 21 (n = 12) vs. 35 +/- 11 (n = 19) bursts/min, P < 0.05], whereas breathing frequency and HR were similar. There was no significant difference between CHF and healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 0 publications
6
91
0
1
Order By: Relevance
“…This approach relies on the assumption that a certain frequency band of HR variability, between 0.04 and 0.35 Hz (18), is modulated by the baroreflex. This construct is based on the coherent relationship between SBP and R-R (or MSNA), each of which oscillate at the same frequency in the power spectrum (2,13,85). Baroreflex sensitivity is expressed by the gain of the transfer function relating changes in blood pressure to coherent changes in R-R or MSNA (2,87,99).…”
Section: Physiology Of the Baroreflex And Methods To Explore Its Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach relies on the assumption that a certain frequency band of HR variability, between 0.04 and 0.35 Hz (18), is modulated by the baroreflex. This construct is based on the coherent relationship between SBP and R-R (or MSNA), each of which oscillate at the same frequency in the power spectrum (2,13,85). Baroreflex sensitivity is expressed by the gain of the transfer function relating changes in blood pressure to coherent changes in R-R or MSNA (2,87,99).…”
Section: Physiology Of the Baroreflex And Methods To Explore Its Funcmentioning
confidence: 99%
“…48, 66), current evidence suggests that the baroreflex contributes substantially to LF oscillations in blood pressure, R-R interval, and MSNA variability (2,13,18,20,108). LF oscillation in the R-R interval has been related to cardiac sympathetic modulation resulting from the baroreflex response to the LF blood pressure oscillations (feedback theory) (108).…”
Section: Arterial Baroreflex and Cardiovascular Variabilitymentioning
confidence: 98%
“…Note that this representation is separate from the negative feedback (Ϫ1) effect, accounting for the "for- 1 This is clearly not the case in all situations, see Limitations. ward" S shape, as opposed to the more familiar reverse S seen more commonly in the baroreflex literature.…”
Section: A Nonlinear Feedback Modelmentioning
confidence: 96%
“…Experiments in a variety of animal models have shown that this oscillation is due to the action of the sympathetic nervous system on the vasculature. Although the oscillation in blood pressure is shifted to 0.4 Hz in the rat (7) and to 0.3 Hz in the rabbit (22), changes in the strength of this oscillation have been proposed to reflect changes in the mean level of sympathetic nerve activity (SNA) and/or baroreflex gain (6), raising the possibility that measurement of the strength of this oscillation may be used as a diagnostic measure of neural control of the cardiovascular system in humans (1,10,26).Current evidence favors the concept of feedback in the baroreflex loop as the origin for the 0.1-Hz oscillation in blood pressure (5,6,13,25,41). In this model, a change in blood pressure is sensed by the arterial baroreceptors altering the afferent signal to the central nervous system (CNS) and subsequently the mean SNA level, which, in turn, alters vascular tone in the target organ.…”
mentioning
confidence: 99%
See 1 more Smart Citation